AI-Driven Management and the Changing Economics of Labor - Dr. Usha N. Patil; Dr. Rajeshkumar U. Sambhe (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
Artificial Intelligence (AI) is no longer just a tool—it is becoming a decision-maker. Across industries, AI-driven systems are taking on core managerial functions, from scheduling and performance evaluation to strategic planning. This transformation is fundamentally reshaping the economics of labor. As AI takes over routine and even complex decision-making tasks, traditional managerial hierarchies are flattening, and the value of human labor is being redefined. While some jobs are being automated away, new roles are emerging that require hybrid skills—blending technical literacy with emotional intelligence and adaptability. This paper explores the shifting dynamics between AI, management, and labor. We examine how AI is changing organizational efficiency, redefining roles, and influencing wage structures. But we also delve into the social and ethical implications: rising inequality, job polarization, increased worker surveillance, and the potential erosion of labor rights. Through analysis of current research, industry practices, and policy debates, this paper offers a nuanced understanding of the risks and opportunities AI brings to the future of work.
Keywords: AI-driven management; Labor transformation; Automation and job displacement; Organizational change; Future of work and ethics